2021
DOI: 10.3390/plants10050856
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Number of Pollen Grains per Male Strobilus in Japanese Cedar (Cryptomeria japonica)

Abstract: Japanese cedar (Cryptomeria japonica) is the most important timber species in Japan; however, its pollen is the primary cause of pollinosis in Japan. The total number of pollen grains produced by a single tree is determined by the number of male strobili (male flowers) and the number of pollen grains per male strobilus. While the number of male strobili is a visible and well-investigated trait, little is known about the number of pollen grains per male strobilus. We hypothesized that genetic and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The cultivars of ND21 showed higher pollen counts than the other four cultivars. It has been reported that oilseed rape pollen counts are affected by genetics (Vonhof et al, 1995;Campos et al, 2021;Kakui et al, 2021) and environmental factors (Hedhly et al, 2005;Jäger et al, 2008;Chaturvedi et al, 2021). A male-sterile line of Brassica napus was found to produce very little pollen and showed no pollen viability, which was also the case in a cytoplasmic male-sterile line with trace pollen (Hou et al, 1991;Hu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The cultivars of ND21 showed higher pollen counts than the other four cultivars. It has been reported that oilseed rape pollen counts are affected by genetics (Vonhof et al, 1995;Campos et al, 2021;Kakui et al, 2021) and environmental factors (Hedhly et al, 2005;Jäger et al, 2008;Chaturvedi et al, 2021). A male-sterile line of Brassica napus was found to produce very little pollen and showed no pollen viability, which was also the case in a cytoplasmic male-sterile line with trace pollen (Hou et al, 1991;Hu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Although the technique developed here is targeted to seeds, it could be used to estimate the number, size, and color of any small particle. For example, ImageJ has been used to manually estimate pollen number and size in flowering plant species (Costa and Yang, 2009 ; Kakui et al, 2021 ), colocalization of organelles within cells (Stauffer et al, 2018 ), and the abundance of scrub typhus cells multiplying under a microscope (Siritantikorn et al, 2012 ). The protocol developed here could be applied to a variety of particles and taxa.…”
Section: Discussionmentioning
confidence: 99%
“…From an evolutionary viewpoint, the number of pollen grains can directly affect seed setting and varies among species and individuals (Tsuchimatsu et al ., 2020). Owing to competition among male gametes, outcrossing plants tend to produce more pollen as compared with self‐fertilizing plants, and wind pollinators tend to produce more pollen than animal‐pollinated species (Kakui et al ., 2021). This is especially critical for maize seed production programmes, in which one plant row is employed to pollinate multiple plant rows used as females.…”
Section: Introductionmentioning
confidence: 99%